Harnessing real-world evidence in pharmacoeconomics: A comprehensive review - Bhatia Nitish (Open Health)
Real-world evidence (RWE) is increasingly recognized as a valuable resource in pharmacoeconomics, offering insights into the effectiveness, safety, and economic impact of healthcare interventions in routine clinical settings. This review highlights the growing significance of RWE beyond traditional clinical trials, focusing on its applications in healthcare decision-making. Key sources of RWE, such as electronic health records, claims data, registries, and observational studies, are explored alongside methodologies like retrospective cohort studies, case–control studies, and comparative effectiveness research. The review examines RWE’s role in assessing treatment effectiveness, estimating healthcare costs, evaluating long-term outcomes, and informing health technology assessments and reimbursement decisions. Challenges such as data quality, confounding factors, and generalizability are discussed with strategies for overcoming these limitations. Regulatory perspectives from agencies like the Food and Drug Administration and European Medicines Agency, as well as ethical and privacy considerations are also reviewed. Emerging trends, such as the integration of artificial intelligence and patient-generated data, offer new opportunities for enhancing the use of RWE in healthcare. The findings emphasize the importance of leveraging RWE to improve healthcare delivery, optimize resource allocation, and support value-based decision-making.